1999
DOI: 10.1207/s15327655jchn1601_1
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Nurses' Knowledge of Lyme Disease: Implications for Surveillance and Community

Abstract: A statewide assessment was conducted to determine the general knowledge and professional practices about Lyme disease (LD) of local health department nurses. The study sample included 226 nurses practicing in 80 health departments in Indiana. Data were collected using a self-administered questionnaire and analyzed using group independent t tests. Findings showed that nurses were most knowledgeable about personal protection against LD and least knowledgeable about symptoms, case definition, and reporting criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Knowledge of tick-borne disease among health professionals should also not be overlooked, as this has been shown to be low, even in endemic areas. This is true of both Lyme disease in North America (Capps et al 1999) and CCHF in Eastern Europe (Rahnavardi et al 2008). Surprisingly, 22% of Turkish health care workers fail to take any precautionary measures when in contact with CCHF patients, despite the contagious nature of the disease (Rahnavardi et al 2008).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Knowledge of tick-borne disease among health professionals should also not be overlooked, as this has been shown to be low, even in endemic areas. This is true of both Lyme disease in North America (Capps et al 1999) and CCHF in Eastern Europe (Rahnavardi et al 2008). Surprisingly, 22% of Turkish health care workers fail to take any precautionary measures when in contact with CCHF patients, despite the contagious nature of the disease (Rahnavardi et al 2008).…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Additionally, Capps et al. (1999) found that nurses are most knowledgeable about personal protection against Lyme disease and should be aware of surveillance, incidence, and prevalence of Lyme disease in their communities. Franklin et al.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence from the scoping review suggests nurses are excellent health educators on ecology, transmission, surveillance, incidence, prevalence, and clinical characteristics of vector‐borne diseases (Audain & Maher, 2017; Capps et al., 1999). Consequently, nurses’ awareness and knowledge of the pathophysiology of vector‐borne diseases is critical (Girard, 2004; Hamlen & Kilman, 2009; Healy, 2000; Laudenslager & Hartung, 2019; Network to Reduce Lyme Disease in School‐Aged Children, Washington, DC, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation